2015
DOI: 10.1128/aem.03575-14
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Surveillance of Poliovirus in Sewage Water around the Introduction Period for Inactivated Polio Vaccine in Japan

Abstract: Environmental virus surveillance was conducted at two independent sewage plants from urban and rural areas in the northern prefecture of the Kyushu district, Japan, to trace polioviruses (PVs) within communities. Consequently, 83 PVs were isolated over a 34-month period from April 2010 to January 2013. The frequency of PV isolation at the urban plant was 1.5 times higher than that at the rural plant. Molecular sequence analysis of the viral VP1 gene identified all three serotypes among the PV isolates, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 42 publications
6
42
0
Order By: Relevance
“…In particular, the gate-keeper transition mutations appear to endow the highest initial fitness, which drives them to rapid fixation from absent or extremely low levels present in the vaccine stock (Neverov and Chumakov, 2010). This is supported by the fact that all three mutations are already present in viruses excreted by vaccinees 14 days after vaccination, and have been observed previously in viruses from primary vaccinees or in sewage surveillance (Dedepsidis et al, 2006; Macadam et al, 1991; Nakamura et al, 2015). Following this, we propose that replication becomes more efficient, allowing a larger viral population size, which increases the probability of transmission, co-infection and recombination with prevalent HEV-C strains (Jegouic et al, 2009).…”
Section: Resultssupporting
confidence: 73%
“…In particular, the gate-keeper transition mutations appear to endow the highest initial fitness, which drives them to rapid fixation from absent or extremely low levels present in the vaccine stock (Neverov and Chumakov, 2010). This is supported by the fact that all three mutations are already present in viruses excreted by vaccinees 14 days after vaccination, and have been observed previously in viruses from primary vaccinees or in sewage surveillance (Dedepsidis et al, 2006; Macadam et al, 1991; Nakamura et al, 2015). Following this, we propose that replication becomes more efficient, allowing a larger viral population size, which increases the probability of transmission, co-infection and recombination with prevalent HEV-C strains (Jegouic et al, 2009).…”
Section: Resultssupporting
confidence: 73%
“…The frequency of SL2 detection in both BMFS and twophase samples can provide an important baseline to compare SL2 prevalence and persistence after the switch from trivalent OPV to bivalent OPV. The frequency of SL2 detection was comparable to other settings (Esteves-Jaramillo et al 2014;Nakamura et al 2015;Wahjuhono et al 2014;Wang et al 2014). This may be due to the high rate of PV2 shedding (88%), compared to PV1 (42%) and PV3 (58%) shedding 1 week after OPV use (Laassri et al 2005) as demonstrated by frequent PV2 detection within 3 weeks after OPV use (n = 10) compared to prior to OPV use (n = 32) (SL1: 40% vs. 38%, SL2: 90% vs. 84%, and SL3: 60% vs. 59% in BMFS and two-phase samples, respectively).…”
Section: Virus Detectionsupporting
confidence: 70%
“…As one of the virus that is generally transmitted by the fecal‐oral route, PV surveillance in the stool specimens cannot be ignored. Some of environmental surveillances of PV in water and sewage have been described previously in Brazil, Israel, Japan, Poland, Spain, and USA [Bosch et al, ; Sinclair et al, ; Nakamura et al, ; de et al, ; Fout et al, ] and the detection rates of PV varied from 2.0% to 5.7%. The prevalence of PV in environmental water in Thailand was comparable to that obtained in other countries at 2.0% [Kittigul et al, ; Tansuphasiri et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, environmental surveillance of PV is an additional choice for monitoring PV strains circulating in the population [Kuryk et al, ]. Epidemiological study of PV infection has been focused mainly on the AFP cases and only few studies have been investigated for the PV in environmental sources [Kittigul et al, ; Tansuphasiri et al, ; Bosch et al, ; Sinclair et al, ; Kuryk et al, ; Nakamura et al, ; de et al, ; Fout et al, ]. In Thailand, only few reports of PV detection in environmental water and sewage have been described [Kittigul et al, ; Tansuphasiri et al, ] and there is no data available for PV surveillance in children with diarrhea.…”
Section: Introductionmentioning
confidence: 99%